2020
DOI: 10.1051/matecconf/202032111026
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Titanium Alloy VT8M-1 with Ultrafine-Grained Structure

Abstract: The paper considers the effect of a long-duration heating at a service temperature of 450oC on VT8M-1 with a coarse-grained (CG) and ultrafine-grained (UFG) microstructure. A duplex ultrafine-grained microstructure, composed of equiaxed grains of primary α-phase and an ultrafine constituent of α- and β-phases, was processed by thermal treatment and further rotary swaging. This type of a microstructure demonstrates a best combination of strength and ductility at room temperature in comparison with the CG struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…1b). The average size of grains/subgrains of the secondary α and βphases was 0.3 µm [6]. The electro-microscopic studies of the microstructure of the VT8M-1 alloy after rotary swaging showed the presence of fine particles mainly located on the inter-phase α/β-boundaries (Fig.…”
Section: Results and Their Discussionmentioning
confidence: 95%
“…1b). The average size of grains/subgrains of the secondary α and βphases was 0.3 µm [6]. The electro-microscopic studies of the microstructure of the VT8M-1 alloy after rotary swaging showed the presence of fine particles mainly located on the inter-phase α/β-boundaries (Fig.…”
Section: Results and Their Discussionmentioning
confidence: 95%